Cancer health self‐efficacy improvement in a randomized controlled trial. Issue 3 (20th October 2021) - Leach, Corinne R.; Hudson, Shawna V.; Diefenbach, Michael A.; Wiseman, Kara P.; Sanders, Amy; Coa, Kisha; Chantaprasopsuk, Sicha; Stephens, Robert L.; Alfano, Catherine M.
Abstract : Background: eHealth interventions can help cancer survivors self‐manage their health outside the clinic. Little is known about how best to engage and assist survivors across the age and cancer treatment spectra. Methods: The American Cancer Society conducted a randomized controlled trial that assessed efficacy of, and engagement with, Springboard Beyond Cancer, an eHealth self‐management program for cancer survivors. Intent‐to treat analyses assessed effects of intervention engagement for treatment (on‐treatment vs completed) overall (n = 176; 88 control, 88 intervention arm) and separately by age (<60 years vs older). Multiple imputation was used to account for participants who were lost to follow‐up (n = 41) or missing self‐efficacy data (n = 1) at 3 months follow‐up. Results: Self‐efficacy for managing cancer, the primary outcome of this trial, increased significantly within the intervention arm and for those who had completed treatment (Cohen's d = 0.26, 0.31, respectively). Additionally, participants with moderate‐to‐high engagement in the text and/or web intervention (n = 30) had a significantly greater self‐efficacy for managing cancer‐related issues compared to the control group (n = 68), with a medium effect size (Cohen's d = 0.44). Self‐efficacy did not differ between the intervention and control arm at 3 months post‐baseline. Conclusions: Study results suggest that cancer survivors benefit variably from eHealth tools. To maximize effects of such tools, it is imperative to tailor information to a priori identified survivor subgroups and increase engagement efforts. Abstract : This randomized controlled trial assessed the efficacy of the Springboard Beyond Cancer eHealth program in a sample of 176 cancer survivors. Results demonstrate significant improvement in self‐efficacy for managing cancer issues among the intervention group and no significant change among the control group.